Preface to the proceedings of DHASA2021 (Journal of the Digital Humanities Association of Southern Africa, 2022)
This is the preface to the DHASA2021 proceedings (including Book of Abstracts and RAIL proceedings).
Keywords: DHASA2021; RAIL2021